Nanostructured spinel-type M(M = Mg, Co, Zn)Cr2O4 oxides: novel adsorbents for aqueous Congo red removal. (December 2021) - Gao, H.J.; Wang, S.F.; Fang, L.M.; Sun, G.A.; Chen, X.P.; Tang, S.N.; Yang, H.; Sun, G.Z.; Li, D.F.
Abstract: Nanostructured spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides with novel adsorbents for aqueous Congo red removal were synthesized by a polyacrylamide gel method and studied for their phase structure, microstructure, adsorption performance, and multiferroic behavior. The phase structure and purity analysis revealed that the nanostructured spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides presented a spinel-type cubic structure, and the formation of a secondary phase such as Cr2 O3, MgO, ZnO, or Co3 O4 was not observed. The microstructure characterization confirmed that the spinel-type MCr2 O4 oxides grew from fine spherical particles to large rhomboid particles. Adsorption experiments of spinel-type MCr2 O4 oxides for adsorption of Congo red dye were fitted well with the pseudo-second-order kinetics. The adsorption capacity of the ZnCr2 O4 oxide (44.038 mg/g, pH 7, temperature 28 °C, initial dye concentration 30 mg/L) was found to be higher than that of MgCr2 O4 oxide (43.592 mg/g, pH 7, temperature 28 °C) and CoCr2 O4 oxide (28.718 mg/g, pH 7, temperature 28 °C). The effects of initial adsorbent concentration, initial dye concentration, pH, and temperature between the ZnCr2 O4 oxide and Congo red dye at which optimal removal occurs, were performed. The thermodynamic studies confirmed that a high temperature favors the adsorption of Congo red dye onto ZnCr2 O4 oxide studied. The nanostructured spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides that exhibited high adsorption performance for adsorption of Congo red dye can be ascribed to the synergistic effect of electrostatic interaction, pore filling, and ion exchange. The present work suggested that the nanostructured spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides have excellent adsorption performance and multiferroic behavior, which shows potential applications for removal of the Congo red dye from wastewater, magnetic memory recording media, magnetic sensor, energy collection and conversion device, and read/write memory. Highlights: A polyacrylamide gel method has been used to synthesize the spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides. The adsorption performance and multiferroic behavior of spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides were compared. An adsorption mechanism of spinel-type M(M = Mg, Co, Zn)Cr2 O4 oxides was proposed.